Insights into hookworm prevalence in Asia: a systematic review and meta-analysis. (10th January 2020) - Zibaei, Mohammad; Nosrati, Mohammad Reza Chaechi; Shadnoosh, Farnosh; Houshmand, Elham; Karami, Maryam Fasihi; Rafsanjani, Mandana Khorsandi; Majidiani, Hamidreza; Ghaffarifar, Fatemeh; Cortes, Hélder Carola Espiguinha; Dalvand, Sahar; Badri, Milad
Abstract: Introduction: Hookworm infections are neglected tropical diseases of humans and animals worldwide. A meta-analysis and systematic review was designed to evaluate the prevalence of hookworm infection in animal and human hosts in Asia until July 2018. Methods: The available online articles of five English databases (PubMed, Scopus, Science Direct, Web of Science and Google Scholar) were explored. Results: The most parasitized carnivores were jackal (48%, CI: 4 to 91%), followed by dog (41%, CI: 29 to 53%), cat (26%, CI: 14 to 38%) and the red fox (19%, CI: 13 to 24%). The weighted prevalence of Ancylostoma braziliensis, A. caninum, A. ceylanicum, A. tubaeforme and Uncinaria stenocephala isolated from different canids were found to be 27% (CI: 21 to 33%), 23% (CI: 7.0 to 53%), 24% (CI: 12 to 35%), 44% (CI: 37 to 51%) and 37% (CI: 18 to 55%), respectively. In total, 98 records were obtained for human hookworms from 3209 760 examined individuals and the calculated weighted prevalence in this population was 19% (CI: 17 to 20%). Conclusions: These findings highlight a desirable ecological milieu for parasite survival and transmission in such territories, which implicates revisiting control programs and public health infrastructures in those areas.